A review of research progress on mechanisms of peritoneal fibrosis related to peritoneal dialysis - Li, Jin’e; Liu, Yinghong; Liu, Jianping (Frontiers in Physiology, 2023)
Peritoneal dialysis (PD) is an effective alternative treatment for patients with endstage renal disease (ESRD) and is increasingly being adopted and promoted worldwide. However, as the duration of peritoneal dialysis extends, it can expose problems with dialysis inadequacy and ultrafiltration failure. The exact mechanism and aetiology of ultrafiltration failure have been of great concern, with triggers such as biological incompatibility of peritoneal dialysis solutions, uraemia toxins, and recurrent intraperitoneal inflammation initiating multiple pathways that regulate the release of various cytokines, promote the transcription of fibrosis-related genes, and deposit extracellular matrix. As a result, peritoneal fibrosis occurs. Exploring the pathogenic factors and molecular mechanisms can help us prevent peritoneal fibrosis and prolong the duration of PD.